Gene expression profiles in auricle skin as a possible additional endpoint for determination of sensitizers: A multi-endpoint evaluation of the local lymph node assay. (5th October 2017) - Tsuchiyama, Hiromi; Maeda, Akihisa; Nakajima, Mayumi; Kitsukawa, Mika; Takahashi, Kei; Miyoshi, Tomoya; Mutsuga, Mayu; Asaoka, Yoshiji; Miyamoto, Yohei; Oshida, Keiyu
Highlights: Avoiding false-positives has been a challenge for the LLNA. We investigated several endpoints in the ex vivo LLNA using skin sensitizers and non-sensitizing irritants. Gene expression profiles in auricle skin suggested T cell recruitment, an event in the elicitation phase. The gene expression of CXCL1 and/or CXCL2 could support discrimination of sensitizers in LLNA. Abstract: The murine local lymph node assay (LLNA) is widely used to test chemicals to induce skin sensitization. Exposure of mouse auricle skin to a sensitizer results in proliferation of local lymph node T cells, which has been measured by in vivo incorporation of H 3 -methyl thymidine or 5-bromo-2′-deoxyuridine (BrdU). The stimulation index (SI), the ratio of the mean proliferation in each treated group to that in the concurrent vehicle control group, is frequently used as a regulatory-authorized endpoint for LLNA. However, some non-sensitizing irritants, such as sodium dodecyl sulfate (SDS) or methyl salicylate (MS), have been reported as false-positives by this endpoint. In search of a potential endpoint to enhance the specificity of existing endpoints, we evaluated 3 contact sensitizers; (hexyl cinnamic aldehyde [HCA], oxazolone [OXA], and 2, 4-dinitrochlorobenzene [DNCB]), 1 respiratory sensitizer (toluene 2, 4-diisocyanate [TDI]), and 2 non-sensitizing irritants (MS and SDS) by several endpoints in LLNA. Each test substance was applied to both ears of female CBA/Ca mice daily for 3 consecutive days. The ears and auricle lymph node cells were analyzed on day 5 for endpoints including the SI value, lymph node cell count, cytokine release from lymph node cells, and histopathological changes and gene expression profiles in auricle skin. The SI values indicated that all the test substances induced significant proliferation of lymph node cells. The lymph node cell counts showed no significant changes by the non-sensitizers assessed. The inflammatory findings of histopathology were similar among the auricle skins treated by sensitizers and irritants. Gene expression profiles of cytokines IFN-γ, IL-4, and IL-17 in auricle skin were similar to the cytokine release profiles in draining lymph node cells. In addition, the gene expression of the chemokine CXCL1 and/or CXCL2 showed that it has the potential to discriminate sensitizers and non-sensitizing irritants. Our results suggest that multi-endpoint analysis in the LLNA leads to a better determination of the sensitizing potential of test substances. We also show that the gene expression of CXCL1 and/or CXCL2, which is involved in elicitation of contact hypersensitivity (CHS), can be a possible additional endpoint for discrimination of sensitizing compounds in LLNA.